Performance Investigation of Some Heterojunction TFETs on SELBOX Substrates: Application to Dielectric Modulated Label-Free Biosensors - Singh, Ashish Kumar (IIT(BHU) Varanasi, 2022)
Abstract is available in the content.
Keywords: Performance Investigation; of Some Heterojunction; TFETs on SELBOX Substrates; Application to Dielectric Modulated; Label-Free Biosensors